(untitled) (Scientific journal of the Fergana State University, 2024)
We know that translation is the translation of a text or speech from one language to another while preserving its meaning, tone, literary text and purpose as closely as possible. This process involves not only translating words from one language to another, but also the nuances, cultural references, idiomatic expressions and subtleties inherent in the original text.